Techno-economic and environmental suitability criteria of hydrothermal processes for treating biogenic residues: A SWOT analysis approach. (1st November 2018) - Reißmann, Daniel; Thrän, Daniela; Bezama, Alberto
Abstract: Biogenic residues are valuable resources that could be utilized through appropriate technologies like hydrothermal processes (HTP) that seem to be suitable to transform wet and sludgy biogenic residues into carbon containing materials and fuels. However, this expectation is not sufficiently evaluated so far which is particularly reasoned in missing criteria to assess HTP as options for the management of biogenic residues. In this paper, we present a structured, transferable and transparent approach for developing techno-economic and environmental suitability criteria for currently discussed HTP concepts using methods from strategy development, especially SWOT analysis. For this, a focus group workshop and expert survey with central stakeholder was carried out and enlarged through an extensive scientific literature review to generate a meaningful information basis. The aim is to identify most relevant criteria to assess HTP to each other and to conventional reference systems which reduces uncertainty for future decisions on the suitability of HTP for treating biogenic residues. The results show that especially the Technology Readiness Level (TRL) is of high importance. Next to this, also the production costs, the product potential, the competitive situation on sales markets and the emissions through the process are of high relevance. In following studies, we want to use these criteria for multi-criteria analysis that will be applied on different scenarios for HTP technology development. Highlights: A structured, transferable and objective approach for the derivation of technology assessment criteria is presented. Information are derived from expert estimations, a focus group workshop and a literature review. The information is structured by a SWOT analysis, as comprehensive basis for the derivation of assessment criteria. The approach is applied to derive techno-economic and environmental suitability criteria for Hydrothermal Processes.